Metal binder, preparation method and binding method
By using thermoplastic resin, carbon fiber and thermoplastic elastomer sulfur-based resin, a metal adhesive with excellent processing properties and stable properties was prepared, which solved the problems of unstable performance and insufficient bonding strength of the metal adhesive in the prior art, and achieved efficient and stable metal bonding effect.
Patent Information
- Application Number
- CN202510020757.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The performance of existing metal adhesives is unstable during processing and the bonding force to metal is insufficient, which affects the service life and appearance of the product.
Using thermoplastic resin, carbon fiber and thermoplastic elastomer sulfur-based resin as the main raw materials, a metal binder with excellent processing properties and stable properties is prepared by melting the thermoplastic resin and forming the thermoplastic elastomer sulfur-based resin and combining with the reinforcement of carbon fibers.
It achieves high processing performance and stable performance of metal adhesives, enhances adhesion with metals, and improves product service life and appearance quality.
Smart Images

Figure BDA0005233062160000051 
Figure BDA0005233062160000061 
Figure BDA0005233062160000062
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal adhesive preparation, and in particular relates to a metal adhesive, a preparation method and a bonding method. Background Art
[0002] With the development of society and the improvement of science and technology, people have higher and higher requirements for material strength. Most products are made of metal materials, such as aluminum alloy, stainless steel, zinc alloy, etc. Metal materials have the advantages of high strength, thin thickness, fast heat dissipation, and good texture. In order to achieve a fast and effective connection between metal and other materials, it is mainly through: 1. Structural bonding such as screw holes or buckles. This method is easy to increase weight and requires process operations such as opening holes, which destroys the integrity of the material; 2. Welding. This method is complicated to clamp and fix, and when the thickness of the metal shell is thin, it will affect the appearance of the product and subsequent processing; 3. Adhesive bonding.
[0003] The third method of adhesive bonding is light and easy to construct, so many studies are devoted to bonding metal surfaces with adhesives. For example, patent US2003 / 0135197 discloses a method for connecting metal and polymer surfaces for medical devices by using a coupling agent. The coupling agent contains at least two sets of functional groups having binding affinity with organic compounds and inorganic compounds respectively. The preferred coupling agent has a first functional group that forms a covalent bond with a polymeric material, and a second functional group that forms an ionic bond with a metal such as stainless steel. The coupling agent can be used with or without thermal activation. However, this method still requires the use of a third-party adhesive, and the performance is limited.
[0004] For example, in patent CN201711166435.3, the adhesion to metal is improved by compounding ternary chloroacetic acid resin and fluororesin in the resin, and the tensile shear strength of the polymer resin and the metal can be increased by nearly 70%. However, the ternary chloroacetic acid resin used in this method has poor heat resistance and will partially decompose during the processing, resulting in increased processing difficulty, unstable product performance, and reduced service life. Summary of the invention
[0005] The purpose of the present invention is to provide a metal adhesive, which has the advantages of good processing performance, stable performance of products after bonding, and strong bonding force with metals.
[0006] The invention also provides a method for preparing the metal adhesive.
[0007] The invention also provides a method for bonding the metal adhesive to metal.
[0008] In order to achieve the above object, a technical solution adopted by the present invention is:
[0009] A metal binder, the raw materials of the metal binder include thermoplastic resin, carbon fiber, thermoplastic elastomer sulfur-based resin, and in parts by weight, the raw materials include:
[0010] Thermoplastic resin: 100 parts;
[0011] Carbon fiber: 10-30 parts;
[0012] Thermoplastic elastomer sulfur-based resin: 3 to 15 parts;
[0013] Wherein, the raw materials of the thermoplastic elastomer sulfur-based resin include:
[0014] Thermoplastic elastomer: 100 parts;
[0015] Metal compound: 30-80 parts;
[0016] Sulfur-containing modifier: 20 to 40 parts.
[0017] In some embodiments of the present invention, the thermoplastic resin is a combination of one or more selected from polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyamide, polyoxymethylene, polycarbonate, polyphenylene ether, polysulfone, rubber, polyester, and polyphenylsulfonic acid resin. Thermoplastic resin has the properties of softening when heated and hardening when cooled, no chemical reaction occurs during heating, and this property can be maintained no matter how many times heating and cooling are repeated.
[0018] According to some specific aspects of the present invention, the thermoplastic resin is a polybenzenesulfonic acid resin, and the molecular structure of the polybenzenesulfonic acid resin contains sulfur elements and benzene ring functional groups, and the polybenzenesulfonic acid resin has better mechanical properties and good adhesion to metals.
[0019] According to some specific aspects of the present invention, the polyphenylene sulfonic acid resin includes but is not limited to a combination of one or more selected from polystyrene sulfonic acid resin, polyphenylene sulfide resin, polyphenylene sulfone resin, polyether sulfone resin, and polyaryl sulfone resin.
[0020] According to some specific aspects of the present invention, the polyphenylene sulfonic acid resin is preferably one or more of polyphenylene sulfide resin and polyphenylene sulfone resin, which can achieve better mechanical properties.
[0021] According to some specific aspects of the present invention, the thermoplastic resin has a melt index of 10 to 50 g / 10 min at 235°C and 2.16 kg, and has better processing performance and physical and mechanical properties. Melt index (MI) is the weight value of a thermoplastic melt passing through a standard capillary within ten minutes at a certain temperature and pressure, expressed in (g / 10 min). The larger the MI value, the lower the viscosity and average molecular weight of the raw material, the better the processing performance and the better the fluidity; on the contrary, the smaller the MI value, the larger the viscosity and average molecular weight of the raw material, the worse the processing performance and the worse the fluidity, but the higher the physical and mechanical properties.
[0022] In some embodiments of the present invention, the carbon fiber is mainly composed of carbon elements, has the characteristics of high temperature resistance, friction resistance, heat conduction and corrosion resistance, and can be fibrous in shape and can be processed into various fabrics. The carbon fiber is a combination of one or more selected from powdered carbon fiber, carbon fiber short fiber, carbon fiber long fiber, carbon fiber bundle, carbon fiber cloth, and carbon fiber felt.
[0023] According to some specific aspects of the present invention, for the convenience and uniformity of processing, the carbon fiber is preferably powdered carbon fiber.
[0024] According to some specific aspects of the present invention, the fiber length of the powdered carbon fiber is in the micron level, and powdered carbon fibers of different fiber lengths within the range of 1 to 1000 microns can be mixed and used.
[0025] According to some specific aspects of the present invention, based on 100 parts by weight of the carbon fiber, different amounts of powdered carbon fibers with different fiber lengths are used for mixing uniformity and better mechanical properties.
[0026] Further preferably, the carbon fiber comprises powdered carbon fiber with a fiber length of 30 μm and powdered carbon fiber with a fiber length of 130 μm, wherein the weight proportion of the powdered carbon fiber with a fiber length of 30 μm is 40-95%, and the weight proportion of the powdered carbon fiber with a fiber length of 130 μm is 5-60%. Alternatively, the carbon fiber comprises powdered carbon fiber with a fiber length of 30 μm and powdered carbon fiber with a fiber length of 130 μm, wherein the weight proportion of the powdered carbon fiber with a fiber length of 30 μm is 60-95%, and the weight proportion of the powdered carbon fiber with a fiber length of 130 μm is 5-40%.
[0027] In some embodiments of the present invention, the thermoplastic elastomer includes but is not limited to a combination of one or more selected from styrenes (SBS, SIS, SEBS, SEPS), olefins (TPO, TPV), dienes (TPB, TPI), vinyl chlorides (TPVC, TCPE), urethanes (TPU), polyesters (TPEE), polyamides (TPAE), organic fluorines (TPF), silicones, and ethylenes. The thermoplastic elastomer is a type of elastomer that has the elasticity of rubber at room temperature and can be plasticized and molded at high temperatures. The structural characteristics of the thermoplastic elastomer are resin segments and rubber segments that are composed of different chemical bonds. The resin segment forms physical crosslinking points by virtue of interchain forces, and the rubber segment is a high elastic segment that contributes to elasticity; the physical crosslinking of the plastic segment changes reversibly with temperature changes, showing the plastic processing characteristics of the thermoplastic elastomer.
[0028] According to some specific aspects of the present invention, the thermoplastic elastomer includes a thermoplastic polyamide elastomer, and the thermoplastic polyamide elastomer is a block copolymer including a hard segment and a soft segment, wherein the soft segment is an aliphatic polyester or polyether soft segment, and the hard segment is a polyamide hard segment. The soft segment and the hard segment induce the formation of hard segment and soft segment microregions and produce a microphase separation structure due to thermodynamic incompatibility. The crystalline microregions and hydrogen bonds formed by the hard segment act as physical crosslinking points, and the flexible soft segment is distributed in the amorphous region, giving the product good elasticity.
[0029] According to some specific aspects of the present invention, the soft segment is preferably a polyether block, which has cross-linking toughness and good mechanical properties.
[0030] In some embodiments of the present invention, the metal compound includes one or more of S and N elements, and S and N elements have strong metal adsorption properties.
[0031] According to some specific aspects of the present invention, the metal compound is a combination of one or more selected from sodium sulfide, potassium sulfide, zinc sulfide, magnesium sulfide, ferrous sulfide, manganese sulfide, lead sulfide, cadmium sulfide, antimony sulfide, stannous sulfide, silver sulfide, copper sulfide, mercuric sulfide, calcium sulfide, strontium sulfide, barium sulfide, manganese nitride, tungsten nitride, zirconium nitride, aluminum nitride, lithium nitride, and magnesium nitride.
[0032] According to some specific aspects of the present invention, the metal compound is preferably one or more of cadmium sulfide and zirconium nitride.
[0033] According to some specific aspects of the present invention, the amount of the metal compound is 30 to 80 parts. If the amount is small, the S content is small, the affinity is weakened, and it is not conducive to metal bonding; if the amount is large, it is easy to cause the thermoplastic elastomer to degrade rapidly and reduce the service life.
[0034] According to some specific aspects of the present invention, the amount of the metal compound is 40 to 70 parts.
[0035] In some embodiments of the present invention, the sulfur-containing modifier is a combination of one or more selected from thiourea, disodium lauryl sulfosuccinate, dimethyl sulfoxide, disodium fatty alcohol polyoxyethylene ether (3) sulfosuccinate MES, sodium dodecyl sulfate, and 1-dodecyl mercaptan, which can further bond metals. The sulfur-containing modifier increases the amount of functional groups in the thermoplastic elastomer, bonds components such as the thermoplastic elastomer, metal compounds, and carbon fibers, and enhances the bonding strength of each component.
[0036] According to some specific aspects of the present invention, the sulfur-containing modifier is a combination of one or more selected from thiourea and sodium dodecyl sulfate, which is easy to process and has good thermal stability.
[0037] Another technical solution provided by the present invention is:
[0038] A method for preparing the above-mentioned metal binder comprises:
[0039] First, a thermoplastic elastomer and a sulfur-containing modifier are heated to 200-300° C. and stirred, and then a metal compound is added and the temperature is lowered to obtain a thermoplastic elastomer sulfur-based resin; then the thermoplastic resin is heated to melt, and finally the thermoplastic resin, the thermoplastic elastomer sulfur-based resin and carbon fibers are mixed to obtain the metal binder.
[0040] Another technical solution provided by the present invention is:
[0041] A method for preparing the metal binder comprises:
[0042] Cut the metal adhesive, and bond the metal adhesive to the metal through a hot riveting device at a temperature of 150 to 300° C. and place at room temperature.
[0043] According to some specific aspects of the present invention, the metal product bonded by the metal adhesive is obtained by placing the metal product at room temperature for 24 hours after bonding.
[0044] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0045] The metal adhesive provided by the present invention does not use solvents in the preparation process, and the adhesive has no irritating odor, meeting environmental protection requirements; the metal adhesive is rich in various polar groups, has strong interaction with the metal surface, and is not easy to fall off the metal layer during long-term use; the metal adhesive has good hardness and toughness. DETAILED DESCRIPTION
[0046] The present invention is further described below in conjunction with the illustrated embodiments.
[0047] Provide examples 1-15 and comparative examples 1-5, the raw materials used in each example and comparative example are as follows:
[0048]
Thermoplastic resin
[0049] A1: Polyphenylene sulfide resin, BR-111BL polyphenylene sulfide resin produced by Chevron Phillips, USA, with a melt index of 35.2g / 10min.
[0050] A2: Polyphenylene sulfone resin, ParylsF1350 polyphenylene sulfone resin produced by Guangdong Youju Advanced New Materials Co., Ltd., with a melt index of 18.7g / 10min.
[0051]
Carbon fiber
[0052] B1: powdered carbon fiber, MLD-30 carbon fiber powder produced by Toray Industries, Ltd., Japan, with a fiber length of 30 μm.
[0053] B2: Powdered carbon fiber, MLD-300 carbon fiber powder produced by Toray Industries, Ltd., Japan, with a fiber length of 130 μm.
[0054] Carbon fibers (M1-M3) were prepared by quantitatively weighing and physically mixing according to the formula shown in Table 1, see Table 1.
[0055] Table 1 Ratio of carbon fiber (M1~M3)
[0056] Carbon Fiber Carbon Fiber B1 Weight Carbon Fiber B2 Weight M1 B1 80 B2 20 M2 B1 95 B2 5 M3 B1 60 B2 40
[0057]
Thermoplastic polyamide elastomer
[0058] C1: polyether block polyamide elastomer, PEBAX-4033 polyether block polyamide elastomer produced by Arkema.
[0059] C2: Polyolefin elastomer, POE6102 polyolefin elastomer produced by Exxon.
[0060]
Metal compounds
[0061] D1: Cadmium sulfide, C305399 cadmium sulfide produced by Shanghai Aladdin Biochemical Technology Co., Ltd.
[0062] D2: Zirconium nitride, Z119196 zirconium nitride produced by Shanghai Aladdin Biochemical Technology Co., Ltd.
[0063]
Sulfur-containing modifier
[0064] E1: Thiourea, T400612 thiourea produced by Shanghai Aladdin Biochemical Technology Co., Ltd.
[0065] E2: Sodium dodecyl sulfate, S348686 sodium dodecyl sulfate produced by Shanghai Aladdin Biochemical Technology Co., Ltd.
[0066] Thermoplastic elastomer sulfur-based resin (N1, N3-N10), according to the formula described in Table 2, weigh a certain amount of thermoplastic elastomer and sulfur-containing modifier, heat to 270°C, stir for 1 hour, and mix evenly; then weigh a certain amount of metal compound and add it, continue to stir for 2 hours to mix evenly, and cool to obtain thermoplastic elastomer sulfur-based resin, see Table 2.
[0067] Thermoplastic elastomer sulfur-based resin (N2), according to the formula described in Table 2, weigh a certain amount of thermoplastic elastomer and sulfur-containing modifier, heat to 180°C, stir for 1 hour, and mix evenly; then weigh a certain amount of metal compound and add it thereto, continue stirring for 2 hours to mix evenly, and cool to obtain thermoplastic elastomer sulfur-based resin, see Table 2.
[0068] Table 2 Formulation of thermoplastic elastomer sulfur-based resin (N1 to N10)
[0069]
[0070]
[0071] The raw material formulas of Examples 1-15 and Comparative Examples 1-5 are shown in Table 3.
[0072] Table 3 Raw material formula of Examples 1-15 and Comparative Examples 1-5
[0073]
[0074] Examples 1 to 15, Comparative Examples 1, 2, 4, and 5 are prepared according to the formula shown in Table 3. The preparation process is as follows: weigh a certain amount of thermoplastic resin, heat it to melt, then add thermoplastic elastomer sulfur-based resin and carbon fiber, stir evenly for 2 hours, and cool to obtain a metal adhesive. Next, the above-mentioned metal adhesive is bonded to the metal layer by the following method: wash and dry the bonding surface of the metal (copper sheet), then cut the metal adhesive sample block to make its size fit the bonding surface of the metal, bond the metal adhesive sample block and the copper sheet through a hot riveting device, the hot riveting temperature is 280°C, the bonding area is 2.5mm×2.5mm, and it is placed at room temperature for 24 hours to obtain a metal product bonded by the metal adhesive.
[0075] Comparative Example 3 According to the formula shown in Table 3, the preparation process is as follows: weigh a certain amount of thermoplastic resin, heat it to melt, then add thermoplastic elastomer resin and carbon fiber, stir evenly for 2 hours, and cool to obtain a metal adhesive. Next, the above-mentioned metal adhesive is bonded to the metal layer by the following method: the bonding surface of the metal (copper sheet) is washed and dried, and then the metal adhesive sample is cut to make its size fit the metal bonding surface, and the metal adhesive sample and the copper sheet are bonded by a hot riveting device, the hot riveting temperature is 280°C, the bonding area is 2.5mm×2.5mm, and it is placed at room temperature for 24 hours to obtain a metal product bonded by the metal adhesive.
[0076] The metal binders of Examples 1 to 15 and Comparative Examples 1 to 5 were injection molded into corresponding specimens according to ISO test standards, and then the following tests were performed. Unless otherwise specified, each test was performed at 25° C. The main indicators are as follows:
[0077] 1. Tensile strength: tested according to GB / T 1040.1-2018;
[0078] 2. Elongation at break: Tested according to GB / T 1040-1992;
[0079] 3. Metal bonding strength: Apply pressure at a rate of 10N / min to the copper surface of the prepared metal product until the bonding layer is destroyed and record the magnitude of the destructive force. The greater the force, the higher the bonding strength.
[0080] Table 4 Performance test data of metal binders of Examples 1-15 and Comparative Examples 1-5
[0081]
[0082]
[0083] As shown in Tables 3 and 4, the metal adhesive prepared in the embodiment has better mechanical properties; the metal adhesive prepared in the embodiment has stronger interaction force with the metal and better bonding force.
[0084] In Example 7, the thermoplastic elastomer and the sulfur-containing modifier are heated to 180°C; in Example 8, the thermoplastic elastomer and the sulfur-containing modifier are heated to 270°C. The tensile strength, elongation at break, and metal bonding strength of the metal adhesive of Example 8 are higher than the tensile strength, elongation at break, and metal bonding strength of the metal adhesive of Example 7, respectively.
[0085] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A metal adhesive, characterized in that: The raw materials of the metal binder include thermoplastic resin, carbon fiber, thermoplastic elastomer sulfur-based resin, and in parts by weight, the raw materials include: Thermoplastic resin: 100 parts; Carbon fiber: 10-30 parts; Thermoplastic elastomer sulfur-based resin: 3 to 15 parts; Wherein, the raw materials of the thermoplastic elastomer sulfur-based resin include: Thermoplastic elastomer: 100 parts; Metal compound: 30-80 parts; Sulfur-containing modifier: 20 to 40 parts.
2. The metal adhesive according to claim 1, characterized in that: The thermoplastic elastomer is a combination of one or more selected from styrenes, olefins, dienes, vinyl chlorides, urethanes, polyesters, polyamides, organic fluorines, organic silicons, and ethylenes.
3. The metal adhesive according to claim 2, characterized in that: The thermoplastic elastomer includes a thermoplastic polyamide elastomer, and the thermoplastic polyamide elastomer includes a hard segment and a soft segment, wherein the soft segment is an aliphatic polyester or polyether block segment, and the hard segment is a polyamide hard segment.
4. The metal adhesive according to claim 1, characterized in that: The metal compound includes one or more of S and N elements.
5. The metal adhesive according to claim 1 or 4, characterized in that: The metal compound is a combination of one or more selected from sodium sulfide, potassium sulfide, zinc sulfide, magnesium sulfide, ferrous sulfide, manganese sulfide, lead sulfide, cadmium sulfide, antimony sulfide, stannous sulfide, silver sulfide, copper sulfide, mercuric sulfide, calcium sulfide, strontium sulfide, barium sulfide, manganese nitride, tungsten nitride, zirconium nitride, aluminum nitride, lithium nitride, and magnesium nitride.
6. The metal adhesive according to claim 1, characterized in that: The sulfur-containing modifier is a combination of one or more selected from thiourea, disodium lauryl sulfosuccinate, dimethyl sulfoxide, disodium fatty alcohol polyoxyethylene ether (3) sulfosuccinate, sodium dodecyl sulfate, and 1-dodecyl mercaptan.
7. The metal adhesive according to claim 1, characterized in that: The thermoplastic resin is a combination of one or more selected from polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyamide, polyoxymethylene, polycarbonate, polyphenylene ether, polysulfone, rubber, polyester, and polyphenylene sulfonic acid resin; and\or the polyphenylene sulfonic acid resin is a combination of one or more selected from polystyrene sulfonic acid resin, polyphenylene sulfide resin, polyphenylene sulfone resin, polyether sulfone resin, and polyaryl sulfone resin.
8. The metal adhesive according to claim 1, characterized in that: The carbon fiber is a combination of one or more selected from powdered carbon fiber, short carbon fiber, long carbon fiber, carbon fiber bundle, carbon fiber cloth, and carbon fiber felt.
9. A method for preparing the metal binder according to any one of claims 1 to 8, characterized in that: include: Firstly, a thermoplastic elastomer and a sulfur-containing modifier are heated and stirred, and then a metal compound is added to obtain a thermoplastic elastomer sulfur-based resin; Then the thermoplastic resin is heated to be melted, and finally the thermoplastic resin, the thermoplastic elastomer sulfur-based resin and the carbon fiber are mixed to obtain the metal binder.
10. A method for bonding metal to metal adhesive, characterized in that: The metal adhesive is the metal adhesive according to any one of claims 1 to 8, and the method comprises: bonding the metal adhesive to the metal at a temperature of 150 to 300° C., and then placing the metal adhesive at room temperature to obtain the metal bonded by the metal adhesive.
Citation Information
Patent Citations
Composite material capable of being bonded with metals
CN108530893A
Bonds between metals and polymers for medical devices
US20030135197A1
Laser stripping material as well as preparation method and application thereof
CN111534270A
Detention network
DE202019102091U1
Base material for thermal adhesion
JP2007254719A